Sports and Physical Education - Forms of Socialization - Sorin Dacian BUHAŞ (Editura Universităţii din Oradea, 2015)
Sport and physical activity can provide an appropriate environment for socialization, but it cannot guarantee, however, in a categorical sense (either positively, or negatively) this fact. This is extremely difficult to follow, since it develops on a long period of time. Perhaps there is no causal explanation of the link between the socialization process and physical activity and the fact that practicing physical exercise automatically leads to socialization. In this context, a number of authors have shown some effects of socialization as a result of sports activity, although the topic of socialization through sports is extremely complex. Sports (sports results, specifically) captures people's attention, exerting a tremendous force of social attraction (ex. large reunions in public markets in cases of won football matches). Sports activities influence in a way or another almost all individuals. Sport is present everywhere in contemporary society. With such amplitude it must have a social role, reflecting a number of norms and values present in society and developing, at the same time, specific skills, knowledge, norms and values. The purpose of this essay is to review the specific literature and to highlight the influence of sports on socialization. I will discuss general and methodological concepts basic in the approach of socialization through sports. This environment can include a number of categories (athletes, coaches, managers, fans, etc.), which will determine answers regarding how and with what effect individuals get to be involved in sports.